An overview of speciation and species limits in birds. Issue 2 (19th April 2021) - Winker, Kevin
Abstract: Accurately determining avian species limits has been a challenge and a work in progress for most of a century. It is a fascinating but difficult problem. Under the biological species concept, only lineages that remain essentially independent when they are in sympatry are clearly species. Otherwise, there is no clear line yet found that marks when a pair of diverging lineages (e.g., in allopatry) become different enough to warrant full biological species status. Also, with more data, species limits often require reevaluation. The process of divergence and speciation is itself very complex and is the focus of intense research. Translating what we understand of that process into taxonomic names can be challenging. A series of issues are important. Single-locus criteria are unlikely to be convincing. Genetic independence is not a species limits requirement, but the degree of independence (gene flow) needs to be considered when there is opportunity for gene flow and independence is not complete. Time-based species (limits determined by time of separation) are unsatisfactory, though integrating time more effectively into our datasets is warranted. We need to disentangle data signal due to neutral processes vs. selection and prioritize the latter as the main driver of speciation. Assortative mating is also not likely to be an adequate criterion for determining species limits. Hybridization and gene flow are more important than ever, and there is a condition not being treated evenly in taxonomy: evolutionary trysts of 2 or more lineages stuck together through gene flow just short of speciation over long periods. Comparative methods that use what occurs between good species in contact to infer species limits among allopatric forms remain the gold standard, but they can be inaccurate and controversial. Species-level taxonomy in birds is likely to remain unsettled for some time. While the study of avian speciation has never been more exciting and dynamic, there is no silver bullet for species delimitation, nor is it likely that there will ever be one. Careful work using integrative taxonomy in a comparative framework is the most promising way forward. Lay Summary: The process of population divergence and speciation produces avian diversity but is very complex. I review this process and some of the challenges we have in translating this knowledge into taxonomic names. Natural and sexual selection, gene flow, time, and neutral changes affect lineages differently, creating difficult puzzles for us to solve when asking "Is it a species?" Avian taxonomy will continue to change as we improve our data and analyses and test historic hypotheses about species limits. An integrative approach using diverse datasets in a comparative framework is the most promising way forward.